3D hydrogel-based microcapsules as an in vitro model to study tumorigenicity, cell migration and drug resistance. - Ertekin, Özlem; Monavari, Mahshid; Krüger, René; Fuentes Chandia, Miguel Angel; Parma, Beatrice; Letort, Gaelle; Tripal, Philipp; Boccaccini, Aldo R.; Boßerhoff, Anja Katrin; Ceppi, Paolo; Kappelmann-Fenzl, Melanie; Leal-Egaña, Aldo (Acta Biomaterialia, 2022)
In this work, we analyzed the reliability of alginate-gelatin microcapsules as artificial tumor model. These tumor-like scaffolds are characterized by their composition and stiffness (∼25 kPa), and their capability to restrict -but not hinder- cell migration, proliferation and release from confinement. Hydrogel-based microcapsules were initially utilized to detect differences in mechano-sensitivity between MCF7 and MDA-MB-231 breast cancer cells, and the endothelial cell line EA.hy926. Additionally, we used RNA-seq and transcriptomic methods to determine how the culture strategy (i.e. 2D v/s 3D) may pre-set the expression of genes involved in multidrug resistance, being then validated by performing cytotoxicological tests and assays of cell morphology. Our results show that both breast cancer cells can generate elongated multicellular spheroids inside the microcapsules, prior being released (mimicking intravasation stages), a behavior which was not observed in endothelial cells. Further, we demonstrate that cells isolated from 3D scaffolds show resistance to cisplatin, a process which seems to be strongly influenced by mechanical stress, instead of hypoxia. We finally discuss the role played by aneuploidy in malignancy and resistance to anticancer drugs, based on the increased number of polynucleated cells found within these microcapsules. Overall, our outcomes demonstrate that alginate-gelatin microcapsules represent a simple, yet very accurate tumor-like model, enabling us to mimic the most relevant malignant hints described in vivo, suggesting that confinement and mechanical stress need to be considered when studying pathogenicity and drug resistance of cancer cells in vitro. STATEMENT OF SIGNIFICANCE: In this work, we analyzed the reliability of alginate-gelatin microcapsules as an artificial tumor model. These scaffolds are characterized by their composition, elastic properties, and their ability to restrict cell migration, proliferation, and release from confinement. Our results demonstrate four novel outcomes: (i) studying cell migration and proliferation in 3D enabled discrimination between malignant and non-pathogenic cells, (ii) studying the cell morphology of cancer aggregates entrapped in alginate-gelatin microcapsules enabled determination of malignancy degree in vitro, (iii) determination that confinement and mechanical stress, instead of hypoxia, are required to generate clones resistant to anticancer drugs (i.e. cisplatin), and (iv) evidence that resistance to anticancer drugs could be due to the presence of polynucleated cells localized inside polymer-based artificial tumors.

Adhesion G Protein-Coupled Receptor Gpr126 (Adgrg6) Expression Profiling in Diseased Mouse, Rat, and Human Kidneys - Kösters, Peter; Cazorla Vázquez, Salvador; Krüger, René; Daniel, Christoph; Vonbrunn, Eva; Amann, Kerstin Ute; Engel, Felix (Cells, 2024)
Uncovering the function of understudied G protein-coupled receptors (GPCRs) provides a wealth of untapped therapeutic potential. The poorly understood adhesion GPCR Gpr126 (Adgrg6) is widely expressed in developing kidneys. In adulthood, Gpr126 expression is enriched in parietal epithelial cells (PECs) and epithelial cells of the collecting duct and urothelium. Whether Gpr126 plays a role in kidney disease remains unclear. Here, we characterized Gpr126 expression in diseased kidneys in mice, rats, and humans. RT-PCR data show that Gpr126 expression is altered in kidney disease. A quantitative RNAscope® analysis utilizing cell type-specific markers revealed that Gpr126 expression upon tubular damage is mainly increased in cell types expressing Gpr126 under healthy conditions as well as in cells of the distal and proximal tubules. Upon glomerular damage, an increase was mainly detected in PECs. Notably, Gpr126 expression was upregulated in an ischemia/reperfusion model within hours, while upregulation in a glomerular damage model was only detected after weeks. An analysis of kidney microarray data from patients with lupus nephritis, IgA nephropathy, focal segmental glomerulosclerosis (FSGS), hypertension, and diabetes as well as single-cell RNA-seq data from kidneys of patients with acute kidney injury and chronic kidney disease indicates that GPR126 expression is also altered in human kidney disease. In patients with FSGS, an RNAscope® analysis showed that GPR126 mRNA is upregulated in PECs belonging to FSGS lesions and proximal tubules. Collectively, we provide detailed insights into Gpr126 expression in kidney disease, indicating that GPR126 is a potential therapeutic target.
CRIS-Team Scopus Importer:2024-05-31
Keywords: adhesion GPCR; collecting duct; focal segmental glomerulosclerosis; Gpr126; human; kidney disease; parietal epithelial cell; RNAscope; urothelium

Characterizing Intraindividual Podocyte Morphology In Vitro with Different Innovative Microscopic and Spectroscopic Techniques - Kraus, Annalena; Rose, Victoria; Krüger, René; Sarau, George; Kling, Lasse; Schiffer, Mario; Christiansen, Silke; Müller-Deile, Janina (Cells, 2023)
Podocytes are critical components of the glomerular filtration barrier, sitting on the outside of the glomerular basement membrane. Primary and secondary foot processes are characteristic for podocytes, but cell processes that develop in culture were not studied much in the past. Moreover, protocols for diverse visualization methods mostly can only be used for one technique, due to differences in fixation, drying and handling. However, we detected by single-cell RNA sequencing (scRNAseq) analysis that cells reveal high variability in genes involved in cell type-specific morphology, even within one cell culture dish, highlighting the need for a compatible protocol that allows measuring the same cell with different methods. Here, we developed a new serial and correlative approach by using a combination of a wide variety of microscopic and spectroscopic techniques in the same cell for a better understanding of podocyte morphology. In detail, the protocol allowed for the sequential analysis of identical cells with light microscopy (LM), Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). Skipping the fixation and drying process, the protocol was also compatible with scanning ion-conductance microscopy (SICM), allowing the determination of podocyte surface topography of nanometer-range in living cells. With the help of nanoGPS Oxyo®, tracking concordant regions of interest of untreated podocytes and podocytes stressed with TGF-β were analyzed with LM, SEM, Raman spectroscopy, AFM and SICM, and revealed significant morphological alterations, including retraction of podocyte process, changes in cell surface morphology and loss of cell-cell contacts, as well as variations in lipid and protein content in TGF-β treated cells. The combination of these consecutive techniques on the same cells provides a comprehensive understanding of podocyte morphology. Additionally, the results can also be used to train automated intelligence networks to predict various outcomes related to podocyte injury in the future.
CRIS-Team Scopus Importer:2023-05-26
Keywords: atomic force microscopy; filopodia; foot processes; light microscopy; nanoGPS tracking; podocytes; Raman spectroscopy; scanning electron microscopy; scanning ion-conductance microscopy; single-cell RNA sequencing

Fine particulate matter (PM2.5) induces microRNA-192–5p causing glomerular damage - Yarbakht, Melina; Sarau, George; Xu, Yanyi; Fang, Xinyi; Mirzaei, Zeynab; Krüger, René; Xiao, Yalan; Usman, Arslan; Daniel, Christoph; Schiffer, Mario; Christiansen, Silke; Müller-Deile, Janina (Ecotoxicology and Environmental Safety, 2025)
An association between air pollution and the incidence of membranous glomerulonephritis (MGN) has been shown in epidemiological studies. However, the causality of this relationship and data on potential pathomechanisms are still missing. Anti-phospholipase A2 receptor (PLA2R1) antibodies, upregulation of microRNA-192–5p, and decreased expression of its podocyte target nephronectin (NPNT) in patients with MGN have been shown, but the trigger for these regulations remained unknown. The current study aimed to assay the possible role of PM2.5 in the pathogenesis of MGN. In this study, we characterized particulate matter (PM2.5) collected on air filters in Shanghai by scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray fluorescence, microwave plasma atomic emission spectroscopy, nanoparticle tracking analysis, and Raman spectroscopy. Cultured human podocytes, zebrafish, and mice were exposed to PM2.5 to assess possible effects on glomerular function and ultrastructure. PM2.5 caused a reduction of podocyte-specific markers and upregulation of microRNA-192–5p. Moreover, NPNT/npnt/Npnt were downregulated, while PLA2R1/pla2r1/Pla2r1 were upregulated. PM2.5 was able to cause edema, proteinuria, and glomerular damage with loosening of the glomerular basement membrane and partial podocyte effacement in zebrafish larvae. BulkRNA seq analysis and qPCR of zebrafish larvae showed an increase in inflammatory response and oxidative stress due to the exposure to PM2.5. Long-term exposure of mice to ambient PM2.5 induced glomerular damage, albuminuria, and upregulation of pulmonary microRNA-192–5p. Therefore, air pollution might be involved in developing MGN through inflammatory pathways and the induction of microRNA-192–5p, which targets gene expression important for glomerular cell function.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Air pollution; glomerulus; membranous glomerulonephritis; PM; podocytes; proteinuria; zebrafish model

Hypoxia controls expression of kidney-pathogenic MUC1 variants - Naas, Stephanie; Krüger, René; Knaup, Karl; Naas, Julia; Grampp, Steffen; Schiffer, Mario; Wiesener, Michael; Schödel, Johannes (Life Science Alliance, 2023)
The interplay between genetic and environmental factors influences the course of chronic kidney disease (CKD). In this context, genetic alterations in the kidney disease gene MUC1 (Mucin1) predispose to the development of CKD. These variations comprise the polymorphism rs4072037, which alters splicing of MUC1 mRNA, the length of a region with variable number of tandem repeats (VNTR), and rare autosomal-dominant inherited dominant-negative mutations in or 59 to the VNTR that causes autosomal dominant tubulointerstitial kidney disease (ADTKD-MUC1). As hypoxia plays a pivotal role in states of acute and chronic kidney injury, we explored the effects of hypoxia-inducible transcription factors (HIF) on the expression of MUC1 and its pathogenic variants in isolated primary human renal tubular cells. We defined a HIF-binding DNA regulatory element in the promoter-proximal region of MUC1 from which hypoxia or treatment with HIF stabilizers, which were recently approved for an anti-anemic therapy in CKD patients, increased levels of wild-type MUC1 and the disease-associated variants. Thus, application of these compounds might exert unfavorable effects in patients carrying MUC1 risk variants.
CRIS-Team Scopus Importer:2023-08-11

Hypoxia hits APOL1 in the kidney - Grampp, Steffen; Krüger, René; Lauer, Victoria; Uebel, Sebastian; Knaup, Karl; Naas, Julia; Höffken, Verena; Weide, Thomas; Schiffer, Mario; Naas, Stephanie; Schödel, Johannes (Kidney International, 2023)
Individuals of African ancestry carrying two pathogenic variants of apolipoprotein 1 (APOL1) have a substantially increased risk for developing chronic kidney disease. The course of APOL1 nephropathy is extremely heterogeneous and shaped by systemic factors such as a response to interferon. However, additional environmental factors operating in this second-hit model have been less well defined. Here, we reveal that stabilization of hypoxia-inducible transcription factors (HIF) by hypoxia or HIF prolyl hydroxylase inhibitors activates transcription of APOL1 in podocytes and tubular cells. An active regulatory DNA-element upstream of APOL1 that interacted with HIF was identified. This enhancer was accessible preferentially in kidney cells. Importantly, upregulation of APOL1 by HIF was additive to the effects of interferon. Furthermore, HIF stimulated expression of APOL1 in tubular cells derived from the urine of an individual carrying a risk variant for kidney disease. Thus, hypoxic insults may serve as important modulators of APOL1 nephropathy.
CRIS-Team Scopus Importer:2023-05-26
Keywords: chronic kidney disease; hypoxia; podocyte; transcription regulation

Hypoxia induces polycystin-1 expression in the renal epithelium - Grampp, Steffen; Kraus, Andre; Skoczynski, Kathrin; Schiffer, Mario; Krüger, René; Naas, Stephanie; Schödel, Johannes; Buchholz, Björn (Royal Society Open Science, 2023)
Mutations in polycystin-1 which is encoded by the PKD1 gene are the main causes for the development of autosomal dominant polycystic kidney disease. However, only little is known about the physiological function of polycystin-1 and even less about the regulation of its expression. Here, we show that expression of PKD1 is induced by hypoxia and compounds that stabilize the hypoxia-inducible transcription factor (HIF) 1α in primary human tubular epithelial cells. Knockdown of HIF subunits confirms HIF-1α-dependent regulation of polycystin-1 expression. Furthermore, HIF ChIP-seq reveals that HIF interacts with a regulatory DNA element within the PKD1 gene in renal tubule-derived cells. HIF-dependent expression of polycystin-1 can also be demonstrated in vivo in kidneys of mice treated with substances that stabilize HIF. Polycystin-1 and HIF-1α have been shown to promote epithelial branching during kidney development. In line with these findings, we show that expression of polycystin-1 within mouse embryonic ureteric bud branches is regulated by HIF. Our finding links expression of one of the main regulators of accurate renal development with the hypoxia signalling pathway and provides additional insight into the pathophysiology of polycystic kidney disease.
CRIS-Team Scopus Importer:2023-06-30
Keywords: hypoxia; hypoxia-inducible factor; kidney development; PKD1; polycystic kidney disease; transcription regulation

KidneyGPS: a user-friendly web application to help prioritize kidney function genes and variants based on evidence from genome-wide association studies - Stanzick, Kira J.; Stark, Klaus J.; Gorski, Mathias; Schödel, Johannes; Krüger, René; Kronenberg, Florian; Warth, Richard; Heid, Iris M.; Winkler, Thomas W. (BMC Bioinformatics, 2023)
Background: Genome-wide association studies (GWAS) have identified hundreds of genetic loci associated with kidney function. By combining these findings with post-GWAS information (e.g., statistical fine-mapping to identify independent association signals and to narrow down signals to causal variants; or different sources of annotation data), new hypotheses regarding physiology and disease aetiology can be obtained. These hypotheses need to be tested in laboratory experiments, for example, to identify new therapeutic targets. For this purpose, the evidence obtained from GWAS and post-GWAS analyses must be processed and presented in a way that they are easily accessible to kidney researchers without specific GWAS expertise. Main: Here we present KidneyGPS, a user-friendly web-application that combines genetic variant association for estimated glomerular filtration rate (eGFR) from the Chronic Kidney Disease Genetics consortium with annotation of (i) genetic variants with functional or regulatory effects (“SNP-to-gene” mapping), (ii) genes with kidney phenotypes in mice or human (“gene-to-phenotype”), and (iii) drugability of genes (to support re-purposing). KidneyGPS adopts a comprehensive approach summarizing evidence for all 5906 genes in the 424 GWAS loci for eGFR identified previously and the 35,885 variants in the 99% credible sets of 594 independent signals. KidneyGPS enables user-friendly access to the abundance of information by search functions for genes, variants, and regions. KidneyGPS also provides a function (“GPS tab”) to generate lists of genes with specific characteristics thus enabling customizable Gene Prioritisation (GPS). These specific characteristics can be as broad as any gene in the 424 loci with a known kidney phenotype in mice or human; or they can be highly focussed on genes mapping to genetic variants or signals with particularly with high statistical support. KidneyGPS is implemented with RShiny in a modularized fashion to facilitate update of input data (https://kidneygps.ur.de/gps/). Conclusion: With the focus on kidney function related evidence, KidneyGPS fills a gap between large general platforms for accessing GWAS and post-GWAS results and the specific needs of the kidney research community. This makes KidneyGPS an important platform for kidney researchers to help translate in silico research results into in vitro or in vivo research.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Gene prioritization; GWAS; Kidney function; KidneyGPS; Web application

Partner, Neighbor, Housekeeper and Dimension: 3D versus 2D Glomerular Co-Cultures Reveal Drawbacks of Currently Used Cell Culture Models - Rederer, Anna; Rose, Victoria; Krüger, René; Schmittutz, Linda; Swierzy, Izabela; Fischer, Lena; Thievessen, Ingo; Bauer, Julian; Friedrich, Oliver; Schiffer, Mario; Müller-Deile, Janina (International Journal of Molecular Sciences, 2023)
Signaling-pathway analyses and the investigation of gene responses to different stimuli are usually performed in 2D monocultures. However, within the glomerulus, cells grow in 3D and are involved in direct and paracrine interactions with different glomerular cell types. Thus, the results from 2D monoculture experiments must be taken with caution. We cultured glomerular endothelial cells, podocytes and mesangial cells in 2D/3D monocultures and 2D/3D co-cultures and analyzed cell survival, self-assembly, gene expression, cell–cell interaction, and gene pathways using live/dead assay, time-lapse analysis, bulk-RNA sequencing, qPCR, and immunofluorescence staining. Without any need for scaffolds, 3D glomerular co-cultures self-organized into spheroids. Podocyte- and glomerular endothelial cell-specific markers and the extracellular matrix were increased in 3D co-cultures compared to 2D co-cultures. Housekeeping genes must be chosen wisely, as many genes used for the normalization of gene expression were themselves affected in 3D culture conditions. The transport of podocyte-derived VEGFA to glomerular endothelial cells confirmed intercellular crosstalk in the 3D co-culture models. The enhanced expression of genes important for glomerular function in 3D, compared to 2D, questions the reliability of currently used 2D monocultures. Hence, glomerular 3D co-cultures might be more suitable in the study of intercellular communication, disease modelling and drug screening ex vivo.
Created from Fastlane, Scopus look-up
Keywords: 3D co-culture; bulk-RNA sequencing; cell culture model; cell matrix; cell–cell communication; glomerular spheroids

Reset of inflammatory priming of joint tissue and reduction of the severity of arthritis flares by bromodomain inhibition - Friščić, Jasna; Reinwald, Christiane; Böttcher, Martin; Houtman, Miranda; Euler, Maximilien; Chen, Xi; Walker, Kellie I.; Kirchner, Philipp; Zhu, Honglin; Wirth, Benjamin; Weidner, Daniela; Krüger, René; et al. (Arthritis and Rheumatology, 2023)
Objective: We have recently shown that priming of synovial fibroblasts (SFs) drives arthritis flares. Pathogenic priming of SFs is essentially mediated by epigenetic reprogramming. Bromodomain and extra-terminal motif (BET) proteins translate epigenetic changes into transcription. Here we used a BET inhibitor to target inflammatory tissue priming and reduce flare severity in experimental arthritis. Methods: BALB/c mice were treated intraperitoneally or locally into the paw with I-BET151, which blocks interaction of BET proteins with acetylated histones. Effect of I-BET151 on acute arthritis and/or inflammatory tissue priming was assessed in a model of repeated injections of monosodium urate crystals or zymosan into the paw. I-BET151 was given either from before arthritis induction, at peak inflammation, or after healing of the first arthritis bout. Transcriptomic (RNA-Seq), epigenomic (ATAC-Seq) and functional analysis (invasion, cytokine production, migration, senescence, metabolic flux) was performed on murine and human SFs treated with I-BET151 in vitro or in vivo. Results: Systemic I-BET151 administration did not affect acute inflammation but abolished inflammatory tissue priming and diminished flare severity in both preventive and therapeutic treatment settings. I-BET151 was also effective when applied locally in the joint. BET inhibition also inhibited osteoclast differentiation, while macrophage activation in the joint was not affected. Flare reduction after BET inhibition was mediated, at least in part, by rolling back the primed transcriptional, metabolic and pathogenic phenotype of SFs. Conclusion: Inflammatory tissue priming is dependent on transcriptional regulation by BET proteins, which makes them promising therapeutic targets for preventing arthritis flares in previously affected joints.
CRIS-Team Scopus Importer:2023-01-27

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The renal cancer risk allele at 14q24.2 activates a novel hypoxia-inducible transcription factor-binding enhancer of DPF3 expression - Protze, Johanna; Naas, Stephanie; Krüger, René; Stöhr, Christine; Kraus, Andre; Grampp, Steffen; Schiffer, Mario; Hartmann, Arndt; Wullich, Bernd; Schödel, Johannes; Wiesener, Michael (Journal of Biological Chemistry, 2022)
Evolution of clear cell renal cell carcinoma is guided by dysregulation of hypoxia-inducible transcription factor (HIF) pathways following loss of the von Hippel-Lindau tumor suppressor protein. Renal cell carcinoma (RCC)-associated polymorphisms influence HIF–DNA interactions at enhancers of important oncogenes thereby modulating the risk of developing renal cancer. A strong signal of genome-wide association with RCC was determined for the single nucleotide polymorphism (SNP) rs4903064, located on chr14q.24.2 within an intron of DPF3, encoding for Double PHD Fingers 3, a member of chromatin remodeling complexes; however, it is unclear how the risk allele operates in renal cells. In this study, we used tissue specimens and primary renal cells from a large cohort of RCC patients to examine the function of this polymorphism. In clear cell renal cell carcinoma tissue, isolated tumor cells as well as in primary renal tubular cells, in which HIF was stabilized, we determined genotype-specific increases of DPF3 mRNA levels and identified that the risk SNP resides in an active enhancer region, creating a novel HIF-binding motif. We then confirmed allele-specific HIF binding to this locus using chromatin immunoprecipitation of HIF subunits. Consequentially, HIF-mediated DPF3 regulation was dependent on the presence of the risk allele. Finally, we show that DPF3 deletion in proximal tubular cells retarded cell growth, indicating potential roles for DPF3 in cell proliferation. Our analyses suggest that the HIF pathway differentially operates on a SNP-induced hypoxia-response element at 14q24.2, thereby affecting DPF3 expression, which increases the risk of developing renal cancer.
CRIS-Team Scopus Importer:2022-03-18

When Mechanical Stress Matters: Generation of Polyploid Giant Cancer Cells in Tumor-Like Microcapsules - Antonelli, Yasmin; Krüger, René; Bühler, Adrian; Monavari, Mahshid; Fuentes Chandia, Miguel Angel; Colombo, Federico; Palmisano, Ralf; Boßerhoff, Anja Katrin; Kappelmann-Fenzl, Melanie; Schödel, Johannes; Boccaccini, Aldo R.; Selhuber-Unkel, Christine; et al. (Advanced Functional Materials, 2024)
Biofabrication techniques enable the performance of bioinspired three-dimensional (3D) matrices resembling primary tumors. To validate their reliability, embedded cells may express complex biophysical responses. Among others, the emergence of tumor heterogeneity and the generation of Polyploid Giant Cancer Cells (PGCC), as a result of the mechanical stress, are two of the most challenging hallmarks to resemble in vitro. Here, these phenomena are studied in cells cultured on two-dimensional (2D) flasks, in 3D spheroids, or immobilized within 3D polymer-based tumor-like microcapsules. These results show that cells cultured in 3D microcapsules exhibited an enhanced biomechanical heterogeneity, a higher number of PGCC, and an increased exertion of cell-matrix attachment forces with respect to the other two experimental conditions. Additionally, cells isolated from tumor-like microcapsules redistribute and align the cytoplasmatic protein Caveolin-1, and upregulate markers involved in cell proliferation (i.e., Ki67), metastasis (i.e., TGF-β1, TGF-β-R2), and epithelial to mesenchymal transition, to name a few. These hallmarks are barely described in the past as a result of the confinement and mechanical stress. Thus, in this work it is demonstrated that both the mechanical stress and confinement are required to stimulate cell polyploidy and biomechanical heterogeneity, which can be easily addressed by immobilizing breast cancer cells in tumor-like microcapsules.
CRIS-Team Scopus Importer:2024-02-16
Keywords: 3D cell culture; cancer biomechanics; intratumor heterogeneity; Polyploid giant cancer cells; Tumor-like microcapsules